PRODUCTIVITY AND QUALITY OF GRAIN OF NEW SPRING WHEAT VARIETIES SELECTED BY NEMCHINOVKA - B. P. Loboda; N. V. Davydova (Зерновое хозяйство России)
In Moscow Selection center seven new spring wheat varieties were selected during the last 20 years, which are able to give the harvest of 3,5 – 4,0 t/ha of high quality food grain during the years with various moisture. New varieties ‘Lada’, ‘Amir’, ‘MIS Ester’, ‘Zlata’, ‘Aestina’ and ‘Lyubava’ selected by Nemchinovka are more tolerant to biotic and abiotic stressors. The grain of the varieties contains 15-16 % of protein and 29-31 % of gluten which is characteristic only for strong wheat. Quality of gluten is rather high (48-76 un. of GSm), ‘baking strength’ of the flour is high (295-374 a.p.), the bread volume of 946-1047 cm3 determines high bakery advantages. These varieties are widely extended (on more than 2,5 ml ha) in such regions as Northern, North-Westen, Central, Volga-Vyatsky and Middle-Volga. In this regard Central Chernozemie is becoming a region of high qualitative food grain production.